1985
DOI: 10.1017/s0003581500024690
|View full text |Cite
|
Sign up to set email alerts
|

Excavations on the Sites of the Amphitheatre and Forum-Basilica at Silchester, Hampshire: an Interim Report

Abstract: A research excavation was commenced on the site of the basilica which forms the western side of the forum of Calleva Atrebatum (Silchester, Hants) in IQ80. Its aim is to examine the Late Iron Age and early Roman occupation which, despite extensive Victorian excavations, was preserved beneath the masonry basilica. So far there is evidence of the Iron Age sequence dating back to the last quarter of the first century B.C.; it ends with the construction of a palisade dating to about the time of the Roman conquest.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In contrast, the other great architectural development of the Roman period, public buildings, in particular the forum-basilica complexes, were primarily a feature of the early Roman period Unlike at Silchester, where the forum-basilica complex is given over to industrial purposes in the late Roman period (Fulford 1985), or Wroxeter, where it is burnt down and not replaced (Wacher 1974, 383). But it saw only relatively minor changes to its fabric, so that major capital outlay was confined to the early Roman period, often linking it with a failure of towns and the flight of capital to the countryside (Reece 1980).…”
Section: Developments Over Timementioning
confidence: 99%
“…In contrast, the other great architectural development of the Roman period, public buildings, in particular the forum-basilica complexes, were primarily a feature of the early Roman period Unlike at Silchester, where the forum-basilica complex is given over to industrial purposes in the late Roman period (Fulford 1985), or Wroxeter, where it is burnt down and not replaced (Wacher 1974, 383). But it saw only relatively minor changes to its fabric, so that major capital outlay was confined to the early Roman period, often linking it with a failure of towns and the flight of capital to the countryside (Reece 1980).…”
Section: Developments Over Timementioning
confidence: 99%
“…Evidence from Verulamium suggested that urban-type rebuilding, featuring piped water, was continuing late on in the fifth century, if not beyond. 9 At Silchester, too, signs of sub-Roman occupation down to around AD 500 is gradually accumulating, 10 and it is quite possible that traces elsewhere would be more abundant had they not be removed prematurely in the past by impatient Romanists. At Wroxeter exceptionally careful excavation of the rubble of the Roman baths identified large-scale Roman-type buildings in timber in a sub-Roman context, but with barely any artefacts.…”
mentioning
confidence: 99%
“…Cunliffe and Rowley 1976). The project was eventually completed after seven seasons of excavation in 1986 (Fulford 1985a;forthcoming).…”
mentioning
confidence: 99%